Improvement of the supply chain system for cooked chicken product exported to Japan: A case study in Thailand for this industry - Payongyam P. (2014)
Due to the complexity of food supply chain management, it is difficult to determine precise areas requiring improvement. This paper aims to develop a key problem identification and extraction framework, based on value stream mapping and theory of constraint techniques for food supply chain improvement direction. A case study in Thailand's cooked chicken industry was used to illustrate to this. It is essential to identify and understand the main problems of this chain by focusing on the effects from downstream to upstream and finding opportunities to solve defects. The results indicate that a non-value added step more than 90 % at the processing factory and caused a bottleneck in capacity resource analysis which revealed main problem. © 2010 IEEE.